Opportunity to Sustain Coconut Ecosystem Services through Recycling of the Palm Leaf Litter as Vermicompost: Indian Scenario (A Technology/ Research Note) - Murali Gopal (International Coconut Community Journal, 2010)
Coconut (Cocos nucifera) is one of the important tropical oilseed crops grown in more than 80 countries. It is called the ‘Tree of Life’ because every part of the palm finds one or other use in everyday life. India is one of the leading coconut producing countries in the world and many millions of Indians are dependent on this crop for their livelihood. Many research experiments are in progress to increase the yield of this crop as well as develop post-harvest products that will improve the socio-economic status of the farmers who cultivate it. The coconut cropping system, being unique, offers a wide range of ecosystem services which has not been studied in much detail. A recent paper from Philippines, however, throws some light on the importance of ecosystem services offered by coconut types. In this article we attempt to enunciate the ecosystem services provided by coconut in Indian scenario and the possibility of sustaining it through the recycling of coconut leaf litter as vermicompost.